Electron microscopical studies of vessels in diabetic peripheral neuropathy. Issue 5 (May 1980) - Williams, E; Timperley, W R; Ward, J D; Duckworth, T
Abstract : the results of an electron microscopical study of sural nerve biopsies from 11 patients with diabetic neuropathy are presented. Thrombi were seen in six cases in at least one intraneural vessel; nine cases showed hyperplasia of endothelial cells, and in seven out of these nine the hyperplasia was sufficient to occlude completely the lumen of small vessels; six cases showed degenerate pericytes and endothelial cells, and in some cases endothelial cells had been shed from the vessel wall, exposing the blood within the vessel to the underlying basement membrane; in five cases large lipid droplets were seen within endothelial cells. Abnormalities of the vessel wall would result in decreased fibrinolytic activity and a reduction of the antiplatelet aggregating proprties of the vessel. Desquamation of endothelial cells from the vessel wall, with exposure of platelets to underlying collagen, may act as a trigger for thrombus formation, particularly as the blood of diabetic patients is often in a hypercoagulable state. The significance of hyperplasia of endothelial cells is at present unknown but, once established, this too would result in profound alterations of loal blood flow and ischaemia of nerve. Damage to endothelial cells may also allow seepage of haematological constituents into the vessel wall, resulting in its progressive thickening.